2010
DOI: 10.1111/j.1365-2842.2009.02045.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre‐heating on the viscosity and microhardness of a resin composite

Abstract: The effect of pre-heating resin composite on pre-cured viscosity and post-cured surface hardness was evaluated. Groups of uncured specimens were heated to 60 degrees C and compared with control groups (24 degrees C) with respect to viscosity and surface hardness. Mean (SD) viscosities of the pre-heated specimens (n = 15) were in the range of 285 (13)-377 (11) (Pa) compared with 642 (35)-800 (23) (Pa) at ambient temperature. There was a statistically significant difference between the two groups (P < 0.001). Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
120
0
18

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(141 citation statements)
references
References 18 publications
3
120
0
18
Order By: Relevance
“…In a recent research found that the increase of microhardness of two preheated conventional resin composites at 54 o C in comparison with room temperature specimens ranged from 9.6% to 23.8%. The explanation of this phenomenon may be that preheated RBCs present increased monomer mobility, due to their higher thermal energy, which leads to a lower viscosity and enhanced mobilities of growing chain moieties in the RBC material 37 . As a result, the degree of conversion increases and the surface microhardness, which indirectly expresses this property, also increases.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent research found that the increase of microhardness of two preheated conventional resin composites at 54 o C in comparison with room temperature specimens ranged from 9.6% to 23.8%. The explanation of this phenomenon may be that preheated RBCs present increased monomer mobility, due to their higher thermal energy, which leads to a lower viscosity and enhanced mobilities of growing chain moieties in the RBC material 37 . As a result, the degree of conversion increases and the surface microhardness, which indirectly expresses this property, also increases.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it increases the degree of conversion. The mechanical properties of the resin composite would go up with the increase of degree of conversion [4][5][6] . However, clinically we couldn't light-cure resins immediately after preheating due to the fact that they also have to be filled, carved.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Film thickness, which is normally limitation with restorative composites resins, can be resolved using preheating. [3][4][5][6]13,22,26,46,48] When using EMAX, group E presented a stable SBS values after aging but was still significantly inferior to that of E/S+. This emphasizes the synergetic effect of etching and silane on that specific ceramic.…”
Section: Discussionmentioning
confidence: 99%